Faith and Reason Today. „Fides et Ratio” in Post-modern Era, red. V. Manimala, Indian Philosophical Studies, XIII, The Council for Research in Values and Philosophy: Washington D.C. 2008, ss. 196. - Durda, Arkadiusz (Teologia w Polsce, 2020)
Recenzja książki: Faith and Reason Today. „Fides et Ratio” in Post-modern Era, red. V. Manimala, Indian Philosophical Studies, XIII, The Council for Research in Values and Philosophy: Washington D.C. 2008, ss. 196.